Socio-Religious Context on Living Hadith: Expression of Gratitude in the Community of Kebun Durian - Firman; Yani, Nur Afrina (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
This study explores the concept of living hadith in the socio-religious practices of Kebun Durian Village, focusing on the tradition of animal sacrifice as an expression of gratitude. Unlike the conventional approach to hadith that emphasizes textual and legal interpretations, this research examines how hadith is brought to life through the community’s everyday actions. The tradition in Kebun Durian is unique, as animal sacrifices are performed not only during major Islamic celebrations like Eid al-Adha but also during personal milestones, such as acquiring new possessions or preparing for significant activities. Utilizing a qualitative and phenomenological approach, the study involved direct observations and in-depth interviews with local leaders and traditional practitioners to understand the deeper meanings and procedures behind this practice. The findings reveal that the community perceives hadith as a dynamic guide integrated into their cultural fabric, demonstrating gratitude, charity, and spiritual devotion. This tradition not only strengthens social bonds but also enriches the community’s religious identity, emphasizing the integration of Islamic teachings with local customs.